2021
DOI: 10.3390/ejihpe11030052
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents and Distance Learning during the First Wave of the COVID-19 Pandemic in Italy: What Impact on Students’ Well-Being and Learning Processes and What Future Prospects?

Abstract: Background: This study aimed to analyze the experiences related to distance learning in a large sample of students in upper secondary school during the first wave of the COVID-19 pandemic in Italy and to explore the potentialities of distance learning for students’ well-being. Methods: Between 22 April and 1 May 2020, 1017 students completed an online survey about the characteristics of online didactic, the availability of devices for distance learning, and the psychological experiences related to e-learning. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…Apart from self-rated health, in which female students reported better overall health, they scored significantly lower on all other well-being measures (life satisfaction, and psychological and somatic symptoms) compared to male students. This finding is consistent with other studies showing that females consistently tend to report more mental health problems than males [ 27 , 36 , 37 , 38 ] The males’ poorer self-rated health could reflect the specific conditions of the pandemic in which social distancing restrictions have lessened their physical activity levels and increased their sedentary behavior, all which are associated with poorer health [ 39 , 40 , 41 , 42 ].…”
Section: Discussionsupporting
confidence: 91%
“…Apart from self-rated health, in which female students reported better overall health, they scored significantly lower on all other well-being measures (life satisfaction, and psychological and somatic symptoms) compared to male students. This finding is consistent with other studies showing that females consistently tend to report more mental health problems than males [ 27 , 36 , 37 , 38 ] The males’ poorer self-rated health could reflect the specific conditions of the pandemic in which social distancing restrictions have lessened their physical activity levels and increased their sedentary behavior, all which are associated with poorer health [ 39 , 40 , 41 , 42 ].…”
Section: Discussionsupporting
confidence: 91%
“…School closures have ranged from none in a few nations to more than one school year in others. At least a third of students are unable to learn remotely due to a lack of connectivity and equipment [10]. Despite the Omicron version, most nations' schools are open with health and safety regulations and immunization regimens in place.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, most instructors did not receive appropriate help from their colleagues. Finally, the COVID-19 outbreak has brought a significant and pressing issue: the impact of school closures and online education on learning and mental health of students [10]. These are unquestionably unusual circumstances that can cause tension and worry in students and instructors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results indicated that females showed more significant psychological negative feelings about the quarantine experience. Similarly, Commodari and La Rosa (2021) examined 1017 secondary school students' distance learning experiences during the first wave of the COVID-19 pandemic in Italy. The results indicated that distance learning was associated with a significant increase in student workload and consequent psychological distress related to homework.…”
Section: A Summary Of the Literaturementioning
confidence: 99%